2009
DOI: 10.3858/emm.2009.41.5.040
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of COTL1 gene identified by proteomic approach and their association with autoimmune disorders

Abstract: To select candidate genes, we attempted to comparative analysis of protein levels between rheumatoid arthritis (RA) patients and healthy controls by two-dimensional electrophoresis (2-DE) and matrix-assisted laser desorption ionization mass spectrometry (MALDI-TOF-MS). We identified 17 proteins that showed up-or down-regulated spots in RA patients. We found that coactosin-like1 (COTL1) were highly expressed in RA patients compared with healthy controls. We performed a case-control study to determine whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…This disease is a rare non-organ specific disorder that occurs in 10 to 50 per 100,000 individuals (Yamada and Yamamoto, 2005). We previously reported that SNPs in the forkhead-box J1 (FOXJ1) and interleukin coactosin-like 1 (COTL1) genes are associated with susceptibility to SLE in a Korean population (Jin et al, 2009;Li et al, 2007). In this study, we evaluated the association between TSLPR polymorphisms and susceptibility to SLE.…”
Section: Discussionmentioning
confidence: 97%
“…This disease is a rare non-organ specific disorder that occurs in 10 to 50 per 100,000 individuals (Yamada and Yamamoto, 2005). We previously reported that SNPs in the forkhead-box J1 (FOXJ1) and interleukin coactosin-like 1 (COTL1) genes are associated with susceptibility to SLE in a Korean population (Jin et al, 2009;Li et al, 2007). In this study, we evaluated the association between TSLPR polymorphisms and susceptibility to SLE.…”
Section: Discussionmentioning
confidence: 97%
“…Leukotrienes are potent mediators of inflammatory disorders, including arthritis, asthma, and allergic reactions. Coactosin is upregulated in rheumatoid arthritis, and polymorphism in the coactosin gene is associated with autoimmune disorders [Jin et al, 2009]. In addition, coactosin is upregulated in peripheral blood leukocytes of patients with Churg–Strauss syndrome, a small‐vessel necrotizing vasculitis [Tougan et al, 2008].…”
Section: Coactosinmentioning
confidence: 99%
“…Recently, the proteomic approach has been successively used to identify the biomarkers in skin, kidney or plasma of SLE patients [5,6,20,21]. However, to the best of our knowledge, no such study has been reported on pSLE patients using sera from north India.…”
Section: Discussionmentioning
confidence: 99%